Health status and medical treatment of the future elderly : final report - Goldman, Dana P. (Dana Paul), 1966- (RAND, 2004)
The ability to predict future health care costs reasonably accurately is critical to planning for the Centers for Medicare and Medicaid Services (CMS). The models used for such projections to date, however, are limited in terms of their capacity to take into account the complex array of factors likely to affect future spending. To improve CMS's ability to map the effects on spending of such factors as medical breakthroughs and demographic trends, RAND Health developed the Future Elderly Model (FEM), a demographic-economic model framework of health spending projections that enables the user to answer "what-if" questions about the effects of changes in health status and disease treatment on future health care costs. What distinguishes the FEM from other models is its inclusion of a multidimensional characterization of health status, which allows the user to include a richer set of demographic controls as well as comorbid conditions and functional status. This report describes the development of the FEM and its application in four clinical areas: cardiovascular disease, the biology of aging and cancer, neurological disease, and changes in health care services. Beside those involved in planning at the Centers for Medicare and Medicaid Services, it should be of interest to health policy planners and health economists.